When Time Binds: Substitutes for Household Production, Returns to Working Long Hours, and the Skilled Gender Wage Gap - Cortés, Patricia; Pan, Jessica (Journal of Labor Economics, 2019)
We provide evidence that constraints that prevent highly skilled women from working long hours hinder gender pay equality. We show that relaxing one such constraint by increasing the supply of substitutes for household production—proxied by intercity variation in predicted low-skilled immigration—increases the relative earnings of women in occupations that disproportionately reward overwork. Low-skilled immigration inflows induce young women to enter occupations with higher returns to overwork and shift women toward higher quantiles of the male wage distribution. The share of women in the top decile remains unaffected, suggesting that other barriers prevent women from reaching the very top.